2012
DOI: 10.1111/fcp.12001
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin added to previously taken antidiabetic agents on insulin resistance and lipid profile: a 2‐year study evaluation

Abstract: The aim of this study was to evaluate whether the positive effects of sitagliptin on glycemic control and insulin resistance were maintained also after 2 years of therapy and whether sitagliptin could be effective also in improving lipid profile. In this randomized, double-blind, placebo-controlled trial, 205 patients with type 2 diabetes in therapy with different antidiabetic drugs were randomized to add sitagliptin 100 mg once a day or placebo to their current therapy. We evaluated at the baseline and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…Gyldenløve M1. et al [28] and Derosa G. et al [29] demonstrated that patients with psoriasis are more insulin resistant compared with healthy control subjects and they showed that sitagliptin is effective in improving the sign of hyperglycemia together with a reduction of insulin resistance. Antiinflammatory effect of sitagliptin on cytokines and natural killer cells in psoriatic lesion might lead to diminution in insulin resistance and hyperglycemia which could be a contributing factor of epidermal cells dysfunction and formation of psoriatic plaques [30].…”
Section: Discussionmentioning
confidence: 99%
“…Gyldenløve M1. et al [28] and Derosa G. et al [29] demonstrated that patients with psoriasis are more insulin resistant compared with healthy control subjects and they showed that sitagliptin is effective in improving the sign of hyperglycemia together with a reduction of insulin resistance. Antiinflammatory effect of sitagliptin on cytokines and natural killer cells in psoriatic lesion might lead to diminution in insulin resistance and hyperglycemia which could be a contributing factor of epidermal cells dysfunction and formation of psoriatic plaques [30].…”
Section: Discussionmentioning
confidence: 99%
“…FBG fasting blood glucose, HOMA-R homeostasis model assessment-R, HOMA-B homeostasis model assessment-B, BMI body mass index, non-HDL-C non-high density lipoprotein cholesterol [20,21], while others reported no such effects [22,23] with sitagliptin. The following reasons can be postulated to explain this discrepancy.…”
Section: Insulin Sensitizing Properties Of Teneligliptin and Sitagliptinmentioning
confidence: 99%
“…In patients initiating sitagliptin, change in body weight was significantly associated with improvements in fasting triglycerides and total cholesterol 60 . When added to previously taken antidiabetic agents, sitagliptin after 2 years of therapy reduced body weight and insulin resistance and improved lipid profile (reduction in total and LDL cholesterol, lowering of triglycerides and augmentation in HDL cholesterol) 80 . A meta-analysis suggested a possible beneficial effect of DPP-4 inhibitors on cholesterol, which, although small, could contribute to the reduction of CV risk 81 .…”
Section: Lipid Profilementioning
confidence: 99%